Implementation of human rights in the context of COVID-19 pandemic - N. R. Chebykina; K. A. Lyamina (Правоприменение)
The subject of the article is the legal basis of human rights and freedoms, including their restriction as one of the aspects of the COVID-19 pandemic. The purpose of the research is to confirm or confute the hypothesis that the restriction of human rights in particular the right to life, the right to health and freedom of movement in Russia during COVID-19 pandemic is legally justified.The methodology of research includes the formal legal interpretation of legal acts as well as the comparative analysis of Russian and foreign legal literature. The authors analyze and interpret international law, including international treaties and the law of foreign states as well as law of the Russian Federation and the constituent entities of the Russian Federation.The main results. Restrictive measures of main human rights may lead to the violation of the constitutional rights and freedoms of citizens, and can also create conditions for abuse of authority while applying the rules governing the emergency situations. International human rights law allows the suspension of certain rights in an emergency that threatens the life of the nation. This can only be done in cases where the emergency has been officially declared, the adoption of emergency measures is caused by an urgent need in the current situation, does not contradict other obligations under international law, is limited in time and does not lead to discrimination. The provisions of the Russian Constitution provide criteria, which observance is mandatory when introducing restrictions on human and civil rights and freedoms. However, no state of emergency was introduced in the Russian Federation. The state has adopted the self-isolation regime that does not have sufficient legal regulation. It has created legal uncertainty. The legal basis of measures to restrict freedom of movement is questionable. It seems these measures go beyond the high-alert regime and require the adoption of regulations that meet the requirements of legislation in the field of emergency situations. The realization of the right to health requires a solution to the problem of coordinating the needs of other patients and patients with COVID-19.Conclusions. Based on the analysis of international law, the law of foreign states and lawmaking activities of state authorities of the Russian Federation in the context of the spread of coronavirus, the authors conclude that the created legal framework for regulating the current situation is characterized by inconsistency, lack of «transparency» and radicality. Unfortunately, the pandemic has shown that regulation in sphere of emergencies, as well as health care, was not fully prepared for active spread of coronovirus. It is necessary to ensure that all emergency measures, including the imposition of a state of emergency, are lawful, proportionate, necessary and non-discriminatory, with a specific purpose and duration.